Design, construction, and evaluation of “sensor lock”: an electromechanical stance control knee joint. - Arazpour, Mokhtar; Ahmadi Bani, Monireh; Baniasad, Mina; Samadian, Mohammad; Golchin, Navid (Disability & Rehabilitation: Assistive Technology, 2018)
Background and aim:Most currently-available stance control knee ankle foot orthoses (SCKAFOs) still need full knee extension to lock the knee joint, and they are still noisy, bulky, and heavy. Therefore, the aim of this study was to design, construct, and evaluate an original electromechanical SCKAFO knee joint that could feasibly solve these problems, and thus address the problems of current stance control knee joints with regards to their structure, function, cosmesis, and cost. Method:Ten able-bodied (AB) participants and two (knee ankle foot orthosis) KAFO users were recruited to participate in the study. A custom SCKAFO with the same set of components was constructed for each participant. Lower limb kinematics were captured using a 6-camera, video-based motion analysis system. Results:For AB participants, significant differences were found between normal walking and walking with the SCKAFO for temporal-spatial parameters and between orthoses with two modes of knee joints in the healthy subjects. Walking with stance control mode produced greater walking speed and step length, greater knee flexion during swing, and less pelvic obliquity than walking with a locked knee, for both AB and KAFO users. Conclusions:The feasibility of this new knee joint with AB people was demonstrated.Implications for rehabilitationStance control knee ankle foot orthoses (SCKAFOs) are designed to stop knee flexion in stance phase and provide free knee movement during swing phase of walking.Due to their high cost, size, excessive weight, and poor performance, few SCKAFO were optimal clinically and commercially.The feasibility of the new knee joint with able-bodied people and poliomyelitis subjects was demonstrated.